Photodynamic therapy in ocular oncology: A bibliometric analysis (1987–2024) - Ceren Türkoğlu; Aslan Aykut (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic therapy (PDT) is a minimally invasive modality widely employed in ocular oncology, utilizing photosensitizers such as verteporfin to induce localized cytotoxic effects. While PDT is commonly applied in the management of benign intraocular tumors and selectively for malignant lesions, bibliometric analyses in this field remain scarce. This study aims to address this gap by analyzing bibliometric trends and mapping the evolution of PDT research in ocular oncology. Methods: A bibliometric analysis was conducted using the Web of Science Core Collection, targeting PDT in ocular tumors. Data were screened for relevance, refined using OpenRefine, and analyzed in Microsoft Excel for publication trends. VOSviewer was used to visualize collaboration networks and keyword co-occurrence. Key indicators such as publication output, citations, authorship, institutional contributions, and journal distribution were assessed. Results: A total of 177 publications (1987–2024) were identified, with original articles comprising 67.7 %. The United States led in publication count (n = 63), total citations (1074), and H-index (20). Investigative Ophthalmology & Visual Science and Retina were the most prolific journals. A decline in publication volume was noted post-2020, coinciding with a global verteporfin shortage. Keyword analysis showed a primary focus on circumscribed choroidal hemangioma, with recent interest shifting toward metastasis and alternative therapies. The most prolific authors were Shields CL and Shields JA, while Schmidt-Erfurth U had the highest citation count. Conclusion: This study presents a comprehensive bibliometric mapping of PDT in ocular oncology, highlighting research trends, influential contributors, and the impact of external factors on scholarly output.